Desperate times call for desperate measures: Government spending multipliers in hard times - Sokbae Lee; Yuan Liao; Myung Hwan Seo; Youngki Shin (Centre for Microdata Methods and Practice (cemmap), 2020)
We investigate state-dependent effects of fiscal multipliers and allow for endogenous sample splitting to determine whether the US economy is in a slack state. When the endogenized slack state is estimated as the period of the unemployment rate higher than about 12 percent, the estimated cumulative multipliers are significantly larger during slack periods than non-slack periods and are above unity. We also examine the possibility of time-varying regimes of slackness and find that our empirical results are robust under a more flexible framework. Our estimation results point out the importance of the heterogenous effects of fiscal policy and shed light on the prospect of fiscal policy in response to economic shocks from the current COVID-19 pandemic.
Keywords: C32; E62; H20; H62; 330; fiscal policy; threshold regression; recession; COVID-19